Observational study to evaluate the safety and efficacy of saroglitazar in Indian diabetic dyslipidemia patients - Shetty, Sadanand R.; Kumar, Soumitra; Mathur, R.P.; Sharma, Kamal H.; Jaiswal, Ashok D. (Indian heart journal, 2015)
Saroglitazar is a dual PPAR α/γ agonist approved in India for the management of diabetic dyslipidemia. The objective of this study was to evaluate the safety and efficacy of saroglitazar 4 mg once daily in clinical practice. This was an observational, multicenter, single-arm study. Patients with type 2 diabetes (with on-going antidiabetic medication), age above 18 years, and triglycerides ≥200 mg/dL were included. A total 2804 patients with a mean duration of diabetes 6.29 yrs were included in this analysis. The baseline demographic profile was: mean age of 53 yrs, mean body weight 72.3 kg and mean BMI of 27 kg/m2. 62.5% patients were male and 57.8% were reported to be on statin therapy at baseline. All 2804 patients were on antidiabetic medications with 15.4% patients on monotherapy and rest were on two or more than two antidiabetic medications at baseline. The baseline triglycerides and HbA1C values were 312.3 mg/dL and 8.3% respectively. At 3 months follow-up, use of saroglitazar 4 mg led to significant reduction in TG (35.8%), LDL-C (16.4%), total cholesterol (19%) and non-HDL-C (23.4%). Addition of saroglitazar to baseline antidiabetic medications showed a significant 0.9% absolute reduction in HbA1c with significant improvement in fasting and post prandial plasma glucose. No serious adverse events, alteration in liver or renal enzymes and edema or weight gain were reported. Saroglitazar is a potential therapeutic option in type 2 diabetic patients with high TG levels, not controlled by statins, for comprehensive control of lipid and glycemic parameters with acceptable safety profile.